Why do we need a policy to deal with sustainable consumption? - Scholl, Gerd; Rubik, Frieder; Kalimo, Harri; Stø, Eivind (Ökologisches Wirtschaften - Fachzeitschrift, 2008)
Current policy instruments are mostly addressing the production and only seldom the consumption of products. Furthermore, the existing policy measures related to consumers are frequently restricted to information. But information is not sufficient to change people’s behavior.